Development of Student Worksheets Based on Comics to Improve Students' Motivation and Learning Outcomes on Material Vibration, Waves and Sound - Niswatul Khaira; Yusrizal Yusrizal; Abdul Gani; Muhammad Syukri; Elisa Elisa; Evendi Evendi (Postgraduate, University of Mataram, 2020)
This research develops a comic-based student worksheet to learn about feasibility, learning outcomes, and motivation of the student worksheet. The research was carried out using research and development (R&D) methods with the ADDIE development model. The implementation of this comic-based Student Worksheet uses a pretest-posttest control group design. The population in this study were students of class VIII at MTsN 3 Banda Aceh. The samples in this study were 57 students in the class of Abu Bakar Ash Siddiq and Zaid bin Thabit who were selected by purposive sampling. Data collection using validation tests, written tests, and questionnaires. The results of the feasibility test showed that the Developed Student Worksheet was included in the feasible category with an average score of assessments by experts and natural science teachers of 91.25% and 99.03%. Analysis of learning outcomes data using the t-test, obtained tcount>ttable (4.42> 2.01) shows that there are differences in the value of student learning outcomes between the experimental and control classes where the value of the experimental class is higher than the control class. Results of analysis Motivation of students tcount>ttable (15,53> 2,01) also shows the use of comic-based worksheets can increase students' learning motivation so that it can be concluded that the use of comic-based worksheets is feasible, it can improve student learning outcomes and motivation